Faktor-faktor Organisasi pada Penyelenggaraan Pendidikan Inklusif di Kecamatan Jelai Hulu Kabupaten Ketapang - Rhendivan Pasaribu (Multiverse: Open Multidisciplinary Journal, 2022)
This study aims to explore the organization of education units and teachers in Jelai Hulu sub-district, Ketapang district in implementing inclusive education and implementation in schools. The population in this quantitative study were junior high school teachers in the Jelai Hulu sub-district, Ketapang district, namely 60 people. as for the sampling based on the purposive sampling method by selecting samples in the form of teachers with civil servant status and contracts totaling 30 people. data analysis using regression analysis. determine the research model and formulate the structural equation in accordance with the proposed research hypothesis. estimate the model parameters by testing the model. Model testing is carried out in three stages, namely evaluation of statistical assumptions, coefficient of determination test, overall test using f test, and individual test using t test. Teacher performance is more focused on the principal's managerial ability and teacher work motivation in an effort to improve the quality of school-based education. The results showed that the overall managerial ability of the principal and work motivation affected the performance of junior high school teachers in the Jelai Hulu sub-district, Ketapang district by 54.5%. the remaining 45.5% is the influence that comes from other factors. for example: school organizational climate, work ethic, organizational culture, principal's performance, satisfaction, loyalty, service, negotiation, quality, and others. Keywords: Teacher Performance, Work Motivation, Managerial Principal